Global Reaction Pathways in the Photodissociation of I3− Ions in Solution at 267 and 400 nm Studied by Picosecond X‐ray Liquidography. Issue 16 (2nd October 2013) - Kim, Kyung Hwan; Ki, Hosung; Oang, Key Young; Nozawa, Shunsuke; Sato, Tokushi; Kim, Joonghan; Kim, Tae Kyu; Kim, Jeongho; Adachi, Shin‐ichi; Ihee, Hyotcherl
Abstract The mechanism of a photochemical reaction involves the formation and dissociation of various short‐lived species on ultrafast timescales and therefore its characterization requires detailed structural information on the transient species. By making use of a structurally sensitive X‐ray probe, time‐resolved X‐ray liquidography (TRXL) can directly elucidate the structures of reacting molecules in the solution phase and thus determine the comprehensive reaction mechanism with high accuracy. In this work, by performing TRXL measurements at two different wavelengths (400 and 267 nm), the reaction mechanism of I3− photolysis, which changes subtly depending on the excitation wavelength, is elucidated. Upon 400 nm photoexcitation, the I3− ion dissociates into I2− and I. By contrast, upon 267 nm photoexcitation, the I3− ion undergoes both two‐body dissociation (I2−+I) and three‐body dissociation (I−+2I) with 7:3 molar ratio. At both excitation wavelengths, all the transient species ultimately disappear in 80 ns by recombining to form the I3− ion nongeminately. In addition to the reaction dynamics of solute species, the results reveal the transient structure of the solute/solvent cage and the changes in solvent density and temperature as a function of time.